Evaluation of Single Surface Atraumatic Restorative Treatment (ART) among 8-12 Year Old Rural School Children of India -A One Year Follow Up Study - V Siva Kalyan; M Shanti; Nusrath Fareed; K M Sudhir; E Venkata Rao; Archana Krishnamurthy (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate survival rate of single surface ART restorations over a period of one year among 8-12 year oldrural school children in India. Materials & Method: A community based interventional study was designed. A total of 147 subjects were included in the study. Baseline data was collected on a specially designed proforma. Treatment was performed following standard procedures for ART using specially designed hand instruments. Evaluations were done at three, six, nine and twelve months intervals. Chi-square was used to test the significance. Results: The mean age of study subjects (147) was 9.69 ΁ 1.3 years. About 84.4% of subjects expressed that they did not had pain I discomfort during treatment; 86.4% of the subjects were willing to undergo theART procedure if required again.Overall survival rate was 91.6% at the end of one year. When the survival rate was compared between permanent and deciduous dentition at the end of 12th month survival rate was high for permanent dentition (95.8%) compared to the deciduousdentition (89.5%). Conclusions: ART was accepted by majority of subjects. Survival rate of single surface ART restorations was extremely good and ART approach can be implemented in schools particularly in the rural areas where there is no adequate access to dental care. ART can be a very strong tool for preventive treatment in the control of dental caries in developing countries.